Genitourinary Foreign Body in United States: Incidence, Patient Characteristics, Treatments and Economic Burden. Issue 6 (November 2019) - Nelson, Marc; Koehne, Elizabeth; Dornbier, Ryan; Perlman, David; Eguia, Emanuel; Sweigert, Patrick; Baker, Marshall; Gupta, Gopal; Baldea, Kristin G.; Farooq, Ahmer
Abstract: Introduction: Genitourinary foreign bodies are uncommon, have only been reported in single center case reports or series and little is known about national incidence. Commonly cited risk factors include psychiatric disorders, drug or alcohol intoxication, or autoerotic stimulation. A population study was performed to characterize the incidence, treatments and economic burden of the genitourinary foreign body. Methods: The Healthcare Cost and Utilization Project Nationwide Inpatient Sample for the years 2012 to 2014 and the Florida State Emergency Department Database and State Inpatient Database for the years 2012 to 2014 were used. Patients were identified as having a diagnosis of genitourinary foreign body by ICD-9 diagnosis codes (939.0, 939.3, 939.9). Patients included in state databases were tracked longitudinally to characterize recurrent visits. Results: Between 2012 and 2014, 1, 125 patients were admitted to United States hospitals with a primary diagnosis of genitourinary foreign body. Patients were predominately male (83.6%) and white race (68.4%). Compared to all other inpatients those with genitourinary foreign body were more likely to have a diagnosis of mental health disease (56.9% vs 30.0%, p <0.005) or substance abuse (11.1% vs 5.9%, p <0.005). Overall 64.9% of patients required operative intervention. Mean adjusted cost per admission was 6, 835 (SD 360), resulting in 2.61 million in annual national economic burden. Conclusions: This study is the first to our knowledge to use population level data to characterize the national incidence and patient characteristics of genitourinary foreign bodies, a condition that costs payers 2.6 million annually.